(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Assisted reproductive technique (ART) has helped couples all over the world. There have already been over 3,500,000 births resulting from ART, and with falling fertility in some countries. Objective: To identify the frequency and types of congenital anomalies among neonates born after ART, and to identify the probable fetal and maternal predisposing factors that may associated with these congenital anormalities and neonatal complications. Methods: This prospective study was performed in the Neonatal Intensive Care Unit in 3 teaching hospitals in Baghdad, from 1st day of January to day 31 of December 2015, and 306 live birth neonates were delivered by ART, and evaluated by the researcher and his residence pediatricians’ doctors, and other congenital anomalies were assessed by ultrasonography, x-ray and echocardiography. Information about each neonate were taken from the records and families which includes: gestational age (term ? 37 week and preterm < 37 week) no post-term case were reported, body-weight (? 2.5 kg and < 2.5 kg), sex, system affected, age of the parents, consanguinity, residence, job of the parents, level of education, health condition of the parents, causes of infertility, any family history of congenital anomalies, death in the family. Exclusion criteria included mothers’ age above 40, any maternal chronic diseases and chronic drugs taken. Congenital anomalies were classified into systems according to WHO recommendation. Results: Three hundred and six neonates were delivered, from which, 30 (10%) had congenital anomalies with male to female ratio (1.2:1), (20 (67%) twins and 10 (33%) were singletons), a significant association between congenital anomalies in ART products and male sex, consanguinity, and gestational age, as the p-value is significant (< 0.05), and the most common system affected was the gastro-intestinal tract (3%), but there was no significant association with body-weight. Conclusion: The ART born neonates are more prone for congenital anomalies. Gastrointestinal anomalies, especially esophageal atresia, are the commonest type of congenital anomalies followed by neurological anomalies. Male sex, consanguinity, and gestational age are significant risk factors for congenital anomalies. While body weight had no significant association with congenital anomalies. Keywords: Assisted reproductive technique (ART), intensive care unit, gastro-intestinal tract. Citation: Deia K. Khalaf. The risk factors and frequency of congenital anomalies in neonates born after assisted reproductive technique in Baghdad. Iraqi JMS. 2017; Vol. 15(4): 339-344. doi: 10.22578/IJMS.15.4.3